2017
DOI: 10.1002/jhet.2797
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic and Grinding Aptitudes of One‐Pot Synthesis of 5‐(4‐Chlorophenyl)‐7‐(3,4‐Dimethyl Phenyl)‐2‐oxo‐2H‐Pyrano[2,3‐b]Pyridine Derivatives as Antibacterial Agents

Abstract: A simple facile “one‐pot” synthesis of 5‐(4‐chlorophenyl)‐7‐(3,4‐dimethyl phenyl)‐2‐oxo‐2H‐pyrano[2,3‐b]pyridine derivatives via three‐component reaction of chalcone, ethyl‐2‐substituted acetate, and ammonium acetate under ultrasonic irradiation and grinding tools. The newly synthesized compounds were evaluated for their antibacterial activity against ATCC 25923, ATCC 10987, ATCC 274, and SM514. All the synthesized compounds have been characterized on the basis of their elemental analyses and spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Moreover, the pyrazole derivatives 5 , 9 , and 14 have controlled growth of pieces of tumors through their combination with triphosphate, and extension during replication leads to lesions and disruptions on DNA strands (Scheme ) . The same mechanism occurred in the 2‐pyrimidinthione derivatives 6 , 11 , and 15 , same with compounds 5 , 6 , 9 , 11 , 15 , and 16 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the pyrazole derivatives 5 , 9 , and 14 have controlled growth of pieces of tumors through their combination with triphosphate, and extension during replication leads to lesions and disruptions on DNA strands (Scheme ) . The same mechanism occurred in the 2‐pyrimidinthione derivatives 6 , 11 , and 15 , same with compounds 5 , 6 , 9 , 11 , 15 , and 16 .…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, the authors reported the reaction of chalcone 1 and ethyl cyanoacetate in the presence of ammonium acetate in a multicomponent reaction (MCR) by mechano‐grindstone all together or by sonication using tetrahydrofuran for 25–30 min to afford crude yellow solid products ( 4a–c ) (Scheme ) .…”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] Substitution of the CH of aryl group by N in position 8 of coumarin, ie, 8-azacoumarin is the most effective planning not only to enhance the hydrophilicity but also to upgrade metabolic stabilization of the antioxidant material. In continuation of our work on MCRs, synthesis of 8-azacoumarin extended the fused heterocycles and significant biological actions [38][39][40] . [30] Specially, 8-azacoumarins display noticeable usage like ascorbic.…”
Section: Introductionmentioning
confidence: 82%
“…The results can be indisputable for the sustainability green synthesis S C H E M E 3 Outline all the produced compounds of the novel azacoumarin derivatives. A mechanistic illustration of the 3CR approach for azacoumarin formation was illustrated as before [38][39][40]. A higher YE is therefore indicative of a higher level of conversion, a much more efficient chemical process and more economical reaction.…”
Section: -7 See More Inmentioning
confidence: 98%
See 1 more Smart Citation